Usability Testing of Medication Packaging in a Pharmacy Environment. (September 2014) - Cluff, Kevin; Mathieu, Mary; Schreiber, Anke; Schulz, Denise; Weller, Amanda; Zhou, Ji
To better understand the pharmacy medication dispensing process and its relationship with packaging and labeling, two studies were conducted: one was a contextual inquiry involving the interview of 13 experienced pharmacists and pharmacy technicians; the other was a usability test of 30 pharmacists and pharmacy technicians specifically related to a particular product family in a simulated pharmacy environment. The interviews of the contextual inquiry provided the basic understanding of the prescription's journey from doctor to patient in the US. The usability study also provided information about a prescription's journey and the importance of safeguards that exist in a real pharmacy environment to prevent dispensing errors.